Analisis Perbandingan Blended Learning berbasis Edmodo dan Google Classroom ditinjau dari Motivasi dan Hasil Belajar Siswa - Maurish Sofie Rahmi Batita; Satrio Hadi Wijoyo; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Vocational high school prepare their students to enter job industry. Industrial work practice or prakerin and implementation of Teaching Factory (TEFA) learning concepts are carried out to bring that vision. Implementation of prakerin must be out ouf school, so it requires e-learning to make learning activities happen. Also, the TEFA learning concept uses block schedule, caused reshuffle of theories based subjects meeting number. This study used quasi experimental to implement blended learning model that could combine face to face meetings and learning activities beyond time and space. Used two e-learning platform, which are edmodo and google classroom, by comparing two variables, which are motivation and learning outcomes. This study revealed that there were significant differences in learning outcomes and motivation between two experimental classes by t-test results. Learning outcomes of blended learning implementation that used Edmodo was better, while Google Classroom was better considering learning motivation.